Energy-Efficient Architectural Design of a Banquet Hall with Integrated Tunnel Ventilation: Monitoring Performance During the Transitional Season in China - Jianwu Xiong; Jing Wu; Jifan Cao; Zexuan Tian; Qianru Yang (Buildings)
The construction industry, a significant contributor to global energy consumption and greenhouse gas emissions, is under considerable pressure to adopt transformative approaches. Public buildings, which account for a substantial portion of total energy usage, must balance high standards of thermal comfort with ventilation efficiency. In China, many public buildings are part of urban landscapes, where façade designs often limit natural ventilation. Consequently, technologies like earth-to-air heat exchangers and wind towers are increasingly essential for enhancing natural ventilation. However, research on the efficacy of these systems remains sparse. This study examines the transitional seasonal environment by evaluating the thermal-humidity index of a banquet hall equipped with an earth-to-air heat exchanger system. Using DeST software [DeST 2.0], the study simulates indoor natural ventilation, calculates ventilation rates, and assesses residual heat removal efficiency. The system’s performance is also modeled under various thermal design zones. Results demonstrate that under natural ventilation, the system can achieve a residual heat removal efficiency of up to 490%. Simulations across different climate zones indicate that the system performs best in regions with extreme temperature fluctuations, particularly those with hot summers and warm winters. In these areas, the system reduces the annual temperature difference by up to 56.7%, significantly improving thermal comfort and reducing dependency on air conditioning. In contrast, performance in milder regions like Kunming achieves only a 37.5% reduction in temperature difference. Overall, this study provides valuable insights into energy-efficient design strategies and thermal optimization for banquet halls, with significant potential for energy savings and enhanced occupant comfort.